Study the effect of spring length on vibrational capacity of an automobile / Faizul Akmal Ahmad Rodi, Mohd Azlan Mohd Aisa and Azizi Bakar - Ahmad Rodi, Faizul Akmal; Mohd Aisa, Mohd Azlan; Bakar, Azizi (Faculty of Mechanical Engineering, 2003)
This final project is about the study on the effect of spring length on vibration capacity of an automobile. Chapter one is the introduction on general information of automotive suspension system and the project approach. Chapter two gives a basic description on automotive spring and their functions. Chapter three explains about the detail on automotive coil spring. In Chapter four, we explain about the spring vibrations in theory. Chapter five explains information about vehicle vibrations. In chapter six we explain about the theory of suspension. Chapter seven explains about the project discussion. Finally, we explain about the conclusion of the project.